Analisis Beta Karoten dan Vitamin pada Kulit dan Daging Buah Pisang Tongka Langit (Musa Troglodytarum L.) di Kota AmbonAROTEN DAN VITAMIN PADA KULIT DAN DAGING BUAH PISANG TONGKA LANGIT (Musa troglodytarum L.) DI KOTA AMBON - Owend Paul Letelay; Adriana Hiariej; Anneke Pesik (Jurnal Agritechno, 2020)
Banana Tongka Langit with fruit bunches soaring up has varied morphological characters including fruit size (long and short), fruit flesh color (yellow to orange) and different banana peel colors (yellow, yellowish orange, reddish orange, reddish brown, and brown) brownish orange) which indicates the presence of beta carotene content. The purpose of the study was to analyze the content of beta carotene and vitamins in the skin and flesh of the Tongka Langit banana using the High Performance Liquid Chromatography method. The results of the analysis of the highest beta carotene content in long fruit flesh is 65.33 mg / 100 and the lowest in short fruit meat is 22.31 mg / 100g. The most vitamin A found in short fruit skin 2260.63 mg / 100g and long fruit skin has the lowest value. The highest value of Vitamin B content is found in long fruit peels at 0.11 mg / 100g and the lowest in long fruit flesh and short fruit peels at 0.09 mg / 100g. The most vitamin C found in long fruit flesh is 28.48 mg / 100g, and the lowest in long fruit skin is 11.99 mg / 100g. The highest vitamin E was found in long fruit peels at 0.41 mg / 100g and the lowest was in short fruit flesh at 0.21 mg / 100g, while vitamin D was not found in all samples.